Principales enfermedades del cultivo de maracuyá (Passiflora edulis) en la zona de Montalvo, Provincia De Los Ríos - Izurieta Puente, Jefferson Arturo (2020)
The passion fruit is a product originating from Brazil; However, farmers in Montalvo are currently dedicating to the cultivation of this passion fruit as a sustainable economic entity for the population. The passion fruit is an edible berry that requires a phytosanitary control for its evolution, this depends on the applications and dose that is determined according to the biotic and abiotic factors. The control method is essential to combat and prevent diseases in the plantation. Among the main cultural tasks that require cultivation for production are sanitary pruning, removal of excess foliage, drainage of excess water; in addition to executing a fungicide application program, considering the rotation of chemical groups to avoid the appearance of acquired resistant strains. The development of this document was based on the review of different bibliographic materials from web pages, scientific articles, lectures, and research works from various universities in the country. The foundation acquired was carried out through synthesis and analysis, in order to provide relevant information about the diseases that are generated in the passion fruit crop, as well as significant contributions to the prevention and neutralization of threats to a productive harvest. According to the aforementioned, it was determined to improve passion fruit production, the vegetative area requires an appropriate edaphoclimatic environment, as well as the application of fungicides in an adequate quantities and established periods, contributing to the prevention and spread of diseases. On the other hand, the use of control to combat diseases considerably benefits the farmer's economy, generating increased production and economic profitability, contributing to a stable and sustainable standard of living for his family.